Effect of serum inflammatory factors in predicting co‐infection with influenza viruses and Omicron - Chengli Zhang; Wei Wang; Xianglin Luo; Minggang Yin; Xiaolong Guo (Immunity, Inflammation and Disease)
Abstract Objectives To identify the key differences in laboratory indicators between mono‐infection and co‐infection by influenza viruses and Omicron to facilitate timely adjustments in patient treatment strategies. Methods Prealbumin and C‐reactive protein (CRP) levels were analyzed in 161 COVID‐19 cases infected by SARS‐CoV‐2 (wild type), 299 cases infected by Omicron, 95 cases infected by influenza virus A/B (Flu A/B) and 133 co‐infection cases infected with Flu A/B and Omicron. The receiver operating characteristic (ROC) curve and logistic regression equation were used to analyze the clinical predictive capacity of prealbumin and CRP in coinfected patients. Results The co‐infected and wild‐type infected patients had significantly different CRP and prealbumin levels compared to mono‐infected patients with Omicron or Flu A/B (p < .001). The ROC curve results indicated that prealbumin was more efficient than CRP in identifying co‐infection from Omicron (AUC: 0.867 vs. 0.724) or Flu A/B (AUC: 0.797 vs. 0.730), and joint prediction significantly improved the diagnostic ability to discriminate co‐infection from mono‐infection (AUC: 0.934 and 0.887). Conclusion The findings suggest that prealbumin is a valuable indicator that can warn of co‐infection and guide timely treatment decisions. Joint prediction may offer an even more effective diagnostic tool for discriminating co‐infection from mono‐infection.